Models of Understanding Hadith in the Sufism Tradition: An Epistemological Analysis of Bayani, Burhani, and Irfani - Ayu Karina; Darin Rihhadatul ‘Aisy; Rizki Restu Afandi; Rio Kurniawan; Agus Ali Dzawafi (Konsultan Jurnal Ilmiah Indonesia, 2026)
This study aims to analyze the model of hadith understanding in the Sufi tradition through the epistemological approaches of bayani, burhani, and irfani. This research uses a qualitative method with a library research approach, which includes the study of various classical and contemporary literatures in the fields of Islamic epistemology, Sufism, and hadith studies. The results of the study show that the understanding of hadith in the Sufi tradition employs three approaches, namely textual, rational, and spiritual approaches. The integration of these three approaches indicates that the Islamic intellectual tradition possesses a complementary system of knowledge, resulting in a more comprehensive, profound, and contextual understanding of hadith in accordance with the development of knowledge and social life.